Brutal aesthetics : Dubuffet, Bataille, Jorn, Paolozzi, Oldenburg - Foster, Hal, 1955- (Princeton, N.J. : Princeton University Press, 2020)
"Modernisme is een manier om de ons omringende realiteit te overwinnen", zo zei Walter Benjamin, en Hal Foster is op zoek gegaan naar artiesten die deze stelling hard kunnen maken. Zo kwam hij terecht bij de brute personages van Jean Dubuffet, de grotten van Georges Bataille, de schepsels van Asger Jorn, de holle goden van Eduardo Paolozzi en de geweren van Claes Oldenburg: al deze kunstenaars maken op die manier gebruik van hun kunst om de harde realiteit van oorlog, nucleaire wapens, kernenergie, fascisme, nazisme, dictators, barbarisme, ... te overleven, te verwerken, ...
How artists created an aesthetic of “positive barbarism” in a world devastated by World War II, the Holocaust, and the atomic bomb. In Brutal Aesthetics, leading art historian Hal Foster explores how postwar artists and writers searched for a new foundation of culture after the massive devastation of World War II, the Holocaust, and the atomic bomb. Inspired by the notion that modernist art can teach us how to survive a civilization become barbaric, Foster examines the various ways that key figures from the early 1940s to the early 1960s sought to develop a “brutal aesthetics” adequate to the destruction around them. With a focus on the philosopher Georges Bataille, the painters Jean Dubuffet and Asger Jorn, and the sculptors Eduardo Paolozzi and Claes Oldenburg, Foster investigates a manifold move to strip art down, or to reveal it as already bare, in order to begin again. What does Bataille seek in the prehistoric cave paintings of Lascaux? How does Dubuffet imagine an art brut, an art unscathed by culture? Why does Jorn populate his paintings with “human animals”? What does Paolozzi see in his monstrous figures assembled from industrial debris? And why does Oldenburg remake everyday products from urban scrap? A study of artistic practices made desperate by a world in crisis, Brutal Aesthetics is an intriguing account of a difficult era in twentieth-century culture, one that has important implications for our own. Published in association with the National Gallery of Art, Washington, DC. -- Publisher description.
Jean Dubuffet and his brutes -- Georges Bataille and his caves -- Asger Jorn and his creatures -- Eduardo Paolozzi and his hollow gods -- Claes Oldenburg and his ray guns.
Includes bibliographical references and index.
Keywords: 1900-1999.; ART / General; Aesthetics, Modern -- 20th century; Aesthetics, Modern; Art, Modern -- 20th century; Art, Modern; Beeldende kunsten; Civilization in art; Civilization in art; Esthetica